The Implementation of Problem Based Learning Model in Improving Cooperation and Learning Outcomes in Physical Education - Dupri, D; Candra, Oki; Candra, Alfi; Suryani, Desi Alif (Universitas Pendidikan Indonesia, 2020)
The decline in the culture of cooperation has an impact on the decrease of the student learning outcomes. The purpose of this study was to see the increase of critical thinking skill and cooperation in Physical Education and Health students through Problem Based Learning Model in Physical Education learning. The method used in this study was experimental method with the Randomize Pre-test and Post-test Control Group Design. The sampling technique in this study was cluster random sampling. The samples of this study were divided into two classes, namely experimental group and control group. The instrument used to measure cooperation was a questionnaire, while learning outcomes were measured by tests. The analysis of this study used SPSS 22 with t-test. This study concludes that the Problem Base Learning model is able to improve the cooperation among the students and also significantly improves learning outcomes. AbstrakMenurunnya budaya kerjasama yang juga berdampak kepada penurunan hasil belajar mahasiswa. Tujuan penelitian ini adalah untuk melihat peningkatan keterampilan berpikir kritis dan Kerjasama mahasiswa Penjaskesrek melalui model Problem Base Learning pada pembelajaran pendidikan jasmani. Metode yang digunakan dalam penelitian ini adalah metode eksperimen dengan Desain dalam penelitian ini adalah Randomize Pretest and Posttest Control Group Design. Teknik pengambilan sampel dalam penelitian ini di ambil secara Cluster Random Sampling, maka sampel pada penlitian ini menjadi dua kelas yaitu kelompok eksperimen kelas 6F dan kelas 6E menjadi kelompok kontrol. Instrumen yang digunakan untuk mengukur kerjasama dengan menggunakan anket dan hasil belajar dengan tes. Analisis penelitian ini menggunakan SPSS 22 dengan uji t. Penelitian ini menyimpulkan bahwa model Problem Base Learning mampu meningkatkan kemampuan kerjasama pada mahasiswa dan juga meningkatkan hasil belajar yang cukup signifikan.